CLEAN AND HEALTHY BEHAVIOR WITH OREM THEORY APPROACH TO IMPROVE KNOWLEDGE AND ATTITUDES ADOLESCENT ABOUT PREVENTION OF SCABIES IN THE ORPHANAGE - Ari Damayanti Wahyuningrum; Misbahul Subhi (Jurnal Ilmiah Kesehatan Media Husada, 2014)
Scabies is a skin infestation by Sarcoptes scabiei. Several risk factors for scabies infestation is individual personal hygiene and environmental sanitation is not maintained, density, crowding, poverty, lack of knowledge, direct contact with the infested person and use of contaminated equipment. According to Orem theory of self care every individual has the ability to care for themselves so that they can maintain the health and welfare of yourself. The purpose of the study was to investigate knowledge and attitude of adolescent in Nurul Abyadh Orphanage Malang in healthy behavior and on handling scabies. Desain use pre test post test non equivalent control group. The population adolescent Orphanage Nurul Abyadh as the treatment group was 38 respondents and adolescent Orphanage Sunan Ampel as the control group was 29 respondents, taken according to inclusion criteria. Research variables include of knowledge variable and attitude variable. Data were collected using structure questionnaire. Data were then analyzed using level of significance ≤ 0,05. Before and after treatment using analysis of the Wilcoxon and Mc Nemar, treatment and control groups using Mann Whitney and Chi Square.